Biohumoral and endocrine parameters in assessment of surgical trauma in open and laparoscopic cholecystectomy - Radunović Miodrag; Radunović Miroslav; Radunović Mirko; Lazović Ranko; Panić Nikola; Bulajić Milutin (Vojnosanitetski Pregled)
Background/Aim. Every surgical procedure causes metabolic, endocrine, and hemodynamic stress in the organism. The aim of this work was to assess the extent of trauma following each of the two types of cholecystectomy (traditional/open and laparoscopic) by measuring palette of biochemical parameters. Methods. This prospective, single- center study included 120 patients subjected to elective cholecystectomy during the period of one year. Sixty patients were treated laparoscopically and 60 traditionally. Biohumoral and endocrine parameters were determined from 24-hour urine and blood. We measured adrenaline, noradrenaline, metabolites of corticosteroid hormones (17-hydroxyl and 17-keto steroids), C-reactive protein (CRP), albumin, glycemia, creatine-phosphokinase (CPK), lactate-dehydrogenase (LDH), red blood cells sedimentation and serum concentration of potassium. Results. We observed significantly lower levels of adrenaline (p < 0.01), noradrenaline (p < 0.05), dopamine (p < 0.01), 17-hydroxyl (p < 0.01) and 17-keto steroids (p < 0.01), glycemia (p < 0.01), CPK (p < 0.01), LDH (p < 0.01) and red blood cells sedimentation (p < 0.01) following laparoscopic cholecystectomy compared to traditional one. Significant increase in CRP levels was recorded postoperatively in both groups (p < 0.05), as well as significant decrease in serum albumin values (p < 0.05). Duration of the hospitalization following laparoscopic cholecystectomy was significantly shorter (p < 0.01). Conclusion. The intensity of organism response is proportional to the intensity of surgical trauma. Metabolic, tissue and neuroendocrine response of organism to trauma has lower intensity after laparoscopic cholecystectomy.